Digital Leap in Rural Tourism: Adoption Challenges and Outcomes of a SaaS-Based Visitor Platform in an Indonesian Tourism Village - Pramesti, Putu Bunga Chandra Sukma; Narottama, Nararya; Sukana, Made (Journal of Business on Hospitality and Tourism, 2025)
Digital transformation is redefining the operational landscape of community-based tourism, particularly in post-pandemic Southeast Asia. This qualitative case study examines the implementation and impact of the Atourin Visitor Management System (AVMS)—a digital platform offering online ticketing, visitor tracking, and real-time financial reporting—in Kenderan Tourism Village, Bali. Through semi-structured interviews with village managers, Atourin representatives, and tourists, combined with field observations and document analysis, the study investigates how digitalization influences destination management, revenue transparency, and tourist experience. Findings reveal that the AVMS partnership directly contributed to Kenderan’s reclassification from a “developing” to an “advanced” tourism village within one year and supported its placement among the Top 75 in the 2023 Indonesian Tourism Village Award. However, implementation barriers persist, primarily rooted in human resource constraints: elderly POKDARWIS (Tourism Awareness Community) members face difficulties operating the dashboard, and frontline staff struggle to guide tourists due to limited digital literacy and language barriers. The study concludes that while digital tools can catalyze institutional recognition and operational efficiency, their success hinges on capacity-building and contextual adaptation. Strategic recommendations include localized training, iterative system design, and co-creation with community stakeholders.